Avaliação do antígeno rKDDR-Plus para o diagnóstico da Leishmaniose Visceral Canina em abrigos de animais de Aracaju/SE - Gomes, Ana Carolina Amado (2020)
Visceral Leishmaniasis (VL) is a neglected tropical disease that can lead to death if not properly diagnosed and treated. The domestic dog is considered the most important reservoir due to its proximity to man. Correct reservoir diagnosis is important to control disease transmission. In order to improve or diagnose the LV canine, a recombinant antigen was developed consisting of 15.3 repeated motifs and 39 kinin amino acids called rKDDR-Plus. The aim of this study was to evaluate the rKDDR-Plus antigen for the diagnosis of Canine Visceral Leishmaniasis in dogs kept in sheltersin Aracaju / SE. As a gold standard, a PCR for Leishmania sp. The rKDDRPlus immunochromatographic test showed greater sensitivity (57%); compared to DPP BioManguinhos® (45%). Both testicles have the same specificity (69%). The rKDDR-Plus was more accurate in dogs diagnosed with VL in endemic areas when it heard a rapid test and currently uses the screening ELISA rKDDR is more sensitive, 49% with 95% CI: 40.71-57.78; in the ELISA rKDDR-Plus, it showed greater specificity, 81% with 95% CI: 62.12-91.49. When compared to the other two tests, rKDDR-Plus showed the largest area of the ROC curve, followed by Gross Extract and rKDDR. Conclude that rKDDR-Plus can be used as a tool to diagnose a CVL.